Measuring the influence of materials composition on nano scale roughness for wood plastic composites by AFM. (September 2016) - Haq, Shamsul; Srivastava, Rajeev
Highlights: Surface smoothness affected by the formulation materials content. The Surface roughness of the WPCs improved with increasing wood flour content. Recycle PP composites showed a better result in comparison to virgin PP composite. Coupled composite have the highest smoothness. 2D roughness profile, 3D surface variations, and FESEM analysis result also for the same. Abstract: Composition of mango wood Polypropylene composites (WPCs) are prepared through melt compounding with the help of micro conical twin screw co-rotating extruder then injection molding of WPCs pellets. Polymer matrix composites are formulated for five compositions with a different weight ratio of wood, virgin polypropylene, recycled polypropylene and coupling agent. Average roughness (Ra), mean peak-to-valley height (Rz) and maximum roughness (Rmax) used to evaluate surface characteristics of samples by AFM. Also measures the 3D surface and surface roughness profile to examine the same. Result from this work clearly shows that recycled Polypropylene based composites with and without coupling agent have a smooth surface in comparison with virgin Polypropylene based composites for same operating variable conditions. The surface smoothness of WPCs improved with decreasing of wood flour content for all samples. By addition of coupling agent surface smoothness of the WPCs increases and the value of Ra decrease from 2.17 to 1.04 nm for recycle polypropylene wood based composite. Surface of composites is also examined with the help of FESEM images. FESEM feature proved that MAPP coupled is shown good bonding strength and smoothness in comparison to none coupled composite for the same class.